Aspek Teknis Budidaya dan Profitabilitas Pembesaran Ikan Nila (Oreochromis niloticus) di Fish Factory Iwa-ke Oishi, Bogor, Jawa Barat - Yani Hadiroseyani; Mira Atul Hayati; Apriana Vinasyiam (Jurnal Akuakultur Sungai dan Danau, 2023)
The grow-out phase in tilapia culture (Oreochromis niloticus) is a vital business segmentation because it is the final supply chain for fish at consumption size for the general market. This study aims to analyze the managerial aspect, and business profitability in tilapia grow-out culture at the Iwa-ke Oishi Fish Factory in Bogor, West Java. The experiment collected primary data (water quality measurement) and secondary data (interview). The tilapia grow-out culture was done by six farmers who were responsible for happas and ponds that they managed. The results showed that managerial aspects include work units, each of which has a specific role, for example, aquapartners responsible for fish culture activities and investors who provide venture capital. The two roles were linked through a profit-sharing scheme with Fish Factory Iwa-ke Oishi as the collaboration coordinator. Tilapia cultured had good growth performance, as seen from a high survival rate (70.0-82.8%), supported by good water quality with low concentrations of nitrite and nitrite during the culture period (1.5 mg/day). L and 0 mg/L, respectively). Financially, this activity was profitable and promising (payback period of 0.9 years). However, the profit margin could be improved by reducing the variable costs, such as utilizing natural biota as additional feed for tilapia to decrease the feeding cost.